2014
DOI: 10.3109/14756366.2013.856424
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies raised against 167–180 aa sequence of human carbonic anhydrase XII inhibit its enzymatic activity

Abstract: Human carbonic anhydrase XII (CA XII) is a single-pass transmembrane protein with an extracellular catalytic domain. This enzyme is being recognized as a potential biomarker for different tumours. The current study was aimed to generate monoclonal antibodies (MAbs) neutralizing the enzymatic activity of CA XII. Bioinformatics analysis of CA XII structure revealed surface-exposed sequences located in a proximity of its catalytic centre. Two MAbs against the selected antigenic peptide spanning 167-180 aa sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Although there are no clinical trials that specifically target CA XII to date, a patent was recently filed for 6A10 monoclonal antibody which specifically targets CA XII [ 3 , 103 , 104 ]. Studies have shown that 6A10 has an inhibitory effect on the CA activity of breast cancer cells overexpressing CA XII [ 105 ].…”
Section: Isoform Specific Targeting Of Cas In Cancermentioning
confidence: 99%
“…Although there are no clinical trials that specifically target CA XII to date, a patent was recently filed for 6A10 monoclonal antibody which specifically targets CA XII [ 3 , 103 , 104 ]. Studies have shown that 6A10 has an inhibitory effect on the CA activity of breast cancer cells overexpressing CA XII [ 105 ].…”
Section: Isoform Specific Targeting Of Cas In Cancermentioning
confidence: 99%
“…So far, little success has been made in identifying carbonic anhydrase-binding antibodies that also block CA enzymatic activity. 6A10 was the first and remains the best-described antibody for the inhibition of CA12 hydratase enzyme activity, with a potential biological role in the reduction of tumor growth 15,20,21 . However, only very few antibodies that can specifically bind and inhibit the hydratase activity of CA9 have appeared in the literature, such as the recently described MSC8 antibody 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Since these various compounds have been subject of numerous recent reviews, here we concentrate only on aromatic sulfonamides as CA inhibitors. Supuran’s group also measured the affinity of monoclonal antibodies to target CA isoforms using SFA ( Dekaminavičiūtė et al, 2014 ). In addition to other previously synthesized compounds containing fluorine, our group has identified a series of fluorinated benzenesulfonamides as strong CA IX inhibitors by SFA and have shown a correlation between parameters obtained by enzymatic and biophysical assays ( Dudutienė et al, 2014 ).…”
Section: Ca Inhibitor Assaysmentioning
confidence: 99%